Vaccine escape recombinants emerge after pneumococcal vaccination in the United States - Brueggemann, A; Pai, R; Crook, D; Beall, B (Public Library of Science, 2007)
The heptavalent pneumococcal conjugate vaccine (PCV7) was introduced in the United States (US) in 2000 and has significantly reduced invasive pneumococcal disease; however, the incidence of nonvaccine serotype invasive disease, particularly due to serotype 19A, has increased. The serotype 19A increase can be explained in part by expansion of a genotype that has been circulating in the US prior to vaccine implementation (and other countries since at least 1990), but also by the emergence of a novel "vaccine escape recombinant" pneumococcal strain. This strain has a genotype that previously was only associated with vaccine serotype 4, but now expresses a nonvaccine serotype 19A capsule. Based on prior evidence for capsular switching by recombination at the capsular locus, the genetic event that resulted in this novel serotype/genotype combination might be identifiable from the DNA sequence of individual pneumococcal strains. Therefore, the aim of this study was to characterise the putative recombinational event(s) at the capsular locus that resulted in the change from a vaccine to a nonvaccine capsular type. Sequencing the capsular locus flanking regions of 51 vaccine escape (progeny), recipient, and putative donor pneumococci revealed a 39kb recombinational fragment, which included the capsular locus, flanking regions, and two adjacent penicillin-binding proteins, and thus resulted in a capsular switch and penicillin nonsusceptibility in a single genetic event. Since 2003, 37 such vaccine escape strains have been detected, some of which had evolved further. Furthermore, two new types of serotype 19A vaccine escape strains emerged in 2005. To our knowledge, this is the first time a single recombinational event has been documented in vivo that resulted in both a change of serotype and penicillin nonsusceptibility. Vaccine escape by genetic recombination at the capsular locus has the potential to reduce PCV7 effectiveness in the longer term.